2007
DOI: 10.1128/mcb.01700-06
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Myogenic Specificity within MyoD Are Required for Noncanonical E Box Binding

Abstract: The MyoD family of basic helix-loop-helix (bHLH) transcription factors has the remarkable ability to induce myogenesis in vitro and in vivo. This myogenic specificity has been mapped to two amino acids in the basic domain, an alanine and threonine, referred to as the myogenic code. These essential determinants of myogenic specificity are conserved in all MyoD family members from worms to humans, yet their function in myogenesis is unclear. Induction of the muscle transcriptional program requires that MyoD be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 51 publications
2
48
0
1
Order By: Relevance
“…PCR primers for the ChIP assay were designed to amplify the promoter region (−185 to −1) or a more distally located sequence (−1 565 to −1 447) in the 5′-regulatory region. As expected, MyoD bound to the promoter region containing its binding sites [9,26], but not to the distal sequence, which lacks a binding site ( Figure 4A and 4B). Similarly, strong binding of CIBZ was observed at the promoter region but not at the distal region.…”
Section: Cibz Binds To the Myog Promoter In A Dna Methylationdependenmentioning
confidence: 84%
See 2 more Smart Citations
“…PCR primers for the ChIP assay were designed to amplify the promoter region (−185 to −1) or a more distally located sequence (−1 565 to −1 447) in the 5′-regulatory region. As expected, MyoD bound to the promoter region containing its binding sites [9,26], but not to the distal sequence, which lacks a binding site ( Figure 4A and 4B). Similarly, strong binding of CIBZ was observed at the promoter region but not at the distal region.…”
Section: Cibz Binds To the Myog Promoter In A Dna Methylationdependenmentioning
confidence: 84%
“…Immunoblot data showed that the expression of either CIBZ or MyoD was not greatly changed after the 5-aza-dC treatment (Supplementary information, Figure S3). ChIP analysis revealed that 5-aza-dC treatment almost abolished the binding of CIBZ to the Myog promoter region, but did not weaken the binding of MyoD, which binds to CpG-free E-box motifs at the Myog promoter [9], to this region ( Figure 4C). These results strongly suggest that binding of CIBZ to the Myog promoter is methylationdependent.…”
Section: Cibz Binds To the Myog Promoter In A Dna Methylationdependenmentioning
confidence: 99%
See 1 more Smart Citation
“…Meis1 and Pknox2 are members of a small family of transcription factors that function in skeletal muscle as pioneer transcription factors to stabilize the MyoD/E12 DNA interaction on suboptimal E box sites, such as the E box found on the myogenin promoter (32)(33)(34). Although little is known about the function of Pknox2, it is similar in homology to Meis1 and is highly expressed in skeletal muscle tissue (35).…”
Section: Mef2amentioning
confidence: 99%
“…Furthermore, studies illustrate that two amino acids in the basic domain of MyoD, an alanine and threonine, are essential to activate the transcription of target genes (18,19). Finally, it was shown that the histidine/cysteine-rich and the amphipathic ␣-helix (helix III) domains of MyoD can regulate a subset of genes, distinct from the genes regulated by the classical N-terminal activation domain, through an interaction with the Pbx and Meis homeodomain proteins located adjacent to the myogenin promoter (20,21).…”
mentioning
confidence: 99%